Peningkatan Hasil Belajar Siswa dalam Memahami Spesifikasi dan Karakteristik Kayu Menggunakan Aplikasi Wood Glossary - Fitria, Afiea Nur; Supardji, Supardji (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This article discusses the use of the Wood Glossary app to assist students in understanding the specifications and characteristics of wood. This application is designed to provide clearer and more accessible information about different types of wood, its properties, and its applications in the industrial world. The improvement of student learning outcomes is achieved through the interactive and visual methods offered by the application. Students can learn a variety of wood-related technical terms in a more fun and less monotonous way, as the app provides images, easy-to-understand explanations, and a quick search feature. Research conducted shows that with the use of Wood Glossary, students are not only faster in understanding the material being taught, but also more motivated to learn. The success of this application shows that technology can be an effective tool in supporting the learning process, especially in studying complex topics such as wood specifications and characteristics. Overall, the Wood Glossary app has been proven to improve students' understanding, enrich their learning experience, and help them to better apply the knowledge gained in practical contexts.